Innovation in Manufacturing for Global Competitiveness : Third International Conference on Advanced Manufacturing Technology (ICAMT 2004) :CONFERENCE PROCEEDINGS 11-13 May 2004, Kuala Lumpur, Malaysia - International Conference on Advanced Manufacturing Technology (3rd : 2004 : Kuala Lumpur) 481613; Venkatesh, V. C., editor 231335; Ahmad Faris Ismail, editor 206193; Awaluddin Mohd. Shaharoun, editor 644409; AKM Nurul Amin, editor 644410; Md. Mohafizul Haque, editor 644411; Noordin Mohd. Yusof, editor 238361; Safian Sharif, editor 372470; Shahjahan Mridha, editor 644412; International Islamic University Malaysia. Faculty of Engineering 644408; Universiti Teknologi Malaysia. Faculty of Mechanical Engineering 3711 (Kuala Lumpur, Malaysia : Research Centre International Islamic University Malaysia, 2004)
Esah Hamzah;